1997
DOI: 10.1007/s002560050309
|View full text |Cite
|
Sign up to set email alerts
|

Extensively calcified synovial sarcoma

Abstract: Synovial sarcoma is an uncommon fibroblastic soft tissue neoplasm, commonly arising near, but not necessarily from, the synovium of joint capsules, bursae or tendon sheaths. The radiological diagnosis is difficult. We present a case of synovial sarcoma studied with plain film radiography, CT, and pathology that had an unusual extensive calcification, which complicated its radiological diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…A more favorable prognosis, on the other hand, is linked to extensive calcification and tumor size below 5 cm [31,79]. Notably, Baheti et al found that none of the six patients with calcifications in their study had expired [10].…”
Section: Prognostic Imaging Features On Ct and Mrimentioning
confidence: 80%
“…A more favorable prognosis, on the other hand, is linked to extensive calcification and tumor size below 5 cm [31,79]. Notably, Baheti et al found that none of the six patients with calcifications in their study had expired [10].…”
Section: Prognostic Imaging Features On Ct and Mrimentioning
confidence: 80%
“…been reported to have a better prognosis in some series. 2,4,28 The major drawbacks of our study in general included its retrospective nature, relatively small sample size, and single-centre study. Imaging analysis of our study was limited by the small number of available imaging studies for our patients.…”
Section: Imaging Featuresmentioning
confidence: 98%
“…12). 55 CT better depicts intratumoral calcifications, present in 30% of synovial sarcoma, 56 and bone erosions, seen in 11 to 20% of cases. 57…”
Section: Synovial Sarcomamentioning
confidence: 99%